Pengembangan Media Pembelajaran Audio Visual Pada Matakuliah Teknik Menghias Kain - Kurniati Kurniati; Irmayanti Irmayanti; Rina Mariana (Seminar Nasional LP2M UNM, 2019)
Abstract. This research aims to develop audiovisual learning media on fabric decoration techniques courses. Audiovisual learning media is developed by using video tutorials which contain the delivery of learning materials and the steps for making basic stitches, embroidery and fabrication techniques. The development procedure used follows the Borg and Gall model. The learning media produced arevalidated by the material expert and the media expert. Based on the results of the material validation and material experts, learning media are in a good category. Based on student response questionnaires in small and large scale tests, learning media are included in the excellent category. Student learning outcomes indicate an increase in the good category. The results of the study show that the audiovisual learning media developed is feasible to be used as a learning media in supporting the understanding and improvement of student skills in fabric decorating courses. Keywords: Learning Media, Audiovisual, Fabric Decorating Techniques